Cornus officinalis prior and post-processing: Regulatory effects on intestinal flora of diabetic nephropathy rats - Ju, Cheng-Guo; Zhu, Lin; Wang, Wei; Gao, Hui; Xu, Yu-Bin; Jia, Tian-Zhu (Frontiers in Pharmacology, 2022)
Background: Diabetic nephropathy (DN) is one of the most common and serious chronic complications in the clinic. Cornus officinalis has the effects of replenishing qi and nourishing yin, tonifying liver and kidney, and it is one of the main traditional Chinese medicines used clinically to treat diabetes and its complications. However, the effect and mechanism of Cornus officinalis before and after processing on intestinal flora of diabetic nephropathy need to be further elucidated. Methods: SD rats were randomly divided into a blank group (10 rats) and DN groups (70 rats). After 4 weeks of high-sugar and high-fat diet, the DN rat model was established by intraperitoneal injection of streptozotocin. After successful modeling, the rats were randomly divided into DN model group, irbesartan group (1.35 mg·kg−1), Cornus officinalis group (281.25 mg·kg−1), wine Cornus officinalis group (281.25 mg·kg−1), wine honey Cornus officinalis group (281.25 mg·kg−1), auxiliary wine group (10 ml·kg−1), auxiliary wine honey group (10 ml·kg−1). During the observation of the rats’ general state, after 6 weeks of continuous administration, the fasting blood glucose of rats in each group was detected, and the kidney index was calculated. The serum creatinine levels, urea nitrogen and 24 h urinary microalbumin were detected by enzyme-linked immunosorbent assay. The expression levels of YKL-40, Wnt4, β-catenin and TGF-β1 mRNA in renal tissue were detected by fluorescence quantitative PCR. Hematoxylin-eosin staining was used to observe the changes in renal pathological injury in each group; GC-MS detected the changes of short chain fatty acid content. Feces were collected for 16 s high-throughput sequencing to analyze the effects of Cornus officinalis on the diversity of intestinal flora in DN before and after processing. Results: Compared with the blank group, the serum creatinine, urea nitrogen, 24 h urinary microalbumin, kidney index and fasting blood glucose in the DN model group were significantly increased (p < 0.05). The renal tissue morphology was disordered and a large number of inflammatory cells were infiltrated. The expression of YKL-40, Wnt4, β-catenin and TGF-β1 mRNA was significantly increased (p < 0.05). Compared with the DN model group, the serum creatinine, urea. Nitrogen, 24 h urine microalbumin, kidney index and fasting blood glucose of rats in each administration group were significantly decreased (p < 0.05), and the general condition and pathological renal damage of DN rats were improved. The effect of wine honey Cornus officinalis was the best, and the expression of YKL-40, Wnt4, β-catenin and TGF-β1 mRNA was significantly decreased (p < 0.05). In each administration group, the improvement of the above indicators in the wine honey Cornus officinalis group was significantly better than that in the raw Cornus officinalis group and wine Cornus officinalis group (p < 0.05), There was no significant difference compared with the irbesartan group (p > 0.05). Each administration group had a significant callback effect on the content of short-chain fatty acids in rat feces, with increased intestinal beneficial bacteria and decreased pathogenic bacteria. Compared with the blank group, the abundance of Firmicutes in the DN model group increased, the abundance of Bacteroidetes decreased, and the ratio showed an upward trend in the DN model group decreased. Each administration group could improve the relative abundance of the above intestinal flora in the model group to varying degrees. Conclusion: The processing of Cornus officinalis may improve the renal injury of DN rats by blocking the activation of Wnt/β-catenin signaling pathway, regulating the structural composition of intestinal microorganisms, and ultimately playing a role in renal protection.